Handbook of Secular Bioethics (I). Key issues - María Casado (Col·lecció de Bioètica, 2020)
Bioethics is a field of knowledge that requires plural approaches and solid scientific foundations to analyse with sufficient rigour the ethical, legal and social consequences of biotechnology and biomedicine. For this reason, this Handbook of Secular Bioethics, the result of many years of teaching and research, is designed to provide the necessary information to those interested in the subject. The ultimate aim is to provide arguments and proposals to encourage autonomy and responsibility, so that bioethical decisions enable the construction of a more transparent and democratic society. This perspective explains why the authors advocate the secular paradigm, based on the idea that the human rights acknowledged in international texts must form the universal minimum ethical threshold as a suitable legal and political model to ensure that these debates are productive and plural, and not merely based on beliefs, religious or of any other kind.